Financial Statement Fraud dengan Moderasi Komisaris Independen: Pengujian Fraud Hexagon (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to examine the influence of the fraud hexagon theory, proxied by financial stability, nature of industry, change in auditor, change in director, frequency of CEO’s pictures, and political connection, on financial statement fraud in mining companies listed on the Indonesia Stock Exchange during 2020–2024, with independent commissioners as a moderating variable. The sampling method used was purposive sampling, resulting in 32 companies with 160 observations. This study employed secondary data obtained from annual reports accessed through the Indonesia Stock Exchange (IDX) website. Data analysis was conducted using logistic regression and moderated regression analysis with EViews 12 software at a 5% significance level. The results show that financial stability, frequency of CEO’s pictures, and political connection significantly affect financial statement fraud, while nature of industry, change in auditor, and change in director have no significant effect. In addition, independent commissioners significantly moderate the relationship between financial stability and financial statement fraud.